Essays on art economics - Menconi, Denise (2021)
This thesis applies the Fama-French three-factors model, augmented with Momentum and Liquidity factors, to analyze Art as an Investment. It also compares investing in Art to several other traditional and non-traditional investments. There is evidence that Market and Momentum factors explain the risk premia in some Art subsegments. The Market Beta, in particular, is lower than what is found in the existing literature, whereas the Momentum factor might explain part of the premia of Contemporary Art and Old Masters. There is no evidence, however, that Art and its subsegments command a Liquidity premium. The thesis also discusses the efficient share of Art in a diversified portfolio, and constructs mean-variance efficient portfolios of the different Art subsegments. Moreover, it provides an overview of the role of asymmetric information and other frictions in shaping the structure of the Art market.